Assessment of Ahmad Yani Road Infrastructure in Tegal City as an Urban and Tourism Road Based on Road Safety Inspection - Suprapto Hadi; Mochammad Affan Dahlan; Reffi Nur Hayati; Fajar Firdaus Maulana; Agustin Ratna Indriani (Green Publisher Indonesia, 2026)
Ahmad Yani Street is one of the main roads in Tegal City with a strategic function as a connector between urban areas and tourist destinations. Although classified as an urban road, its existing condition does not fully comply with technical standards. The sidewalks and shoulders are wider than the vehicle lanes, and the one-way traffic system makes the corridor more pedestrian-oriented. This study aims to analyze the suitability of Ahmad Yani Street's function as an urban and tourism road. The research method used was descriptive comparative through field observation, documentation, and analysis based on standards from Bina Marga and the Ministry of Public Works and Housing. The results show that Ahmad Yani Street has more characteristics of a tourism road due to its high aesthetic quality and pedestrian comfort, although the traffic performance for motorized vehicles remains limited. Ahmad Yani Street in Tegal City, with its pedestrian-oriented characteristics and high aesthetic quality, aligns more with the function of a tourism road than an urban road. While it provides comfortable spaces for pedestrians and enhances the tourist experience, the street's infrastructure does not fully meet the technical standards for urban roads, particularly in terms of vehicle lane width and traffic management.